ERP based measures of cognitive workload: A review. (November 2020) - Ghani, Usman; Signal, Nada; Niazi, Imran Khan; Taylor, Denise
Highlights: Single-task event-related potential (ERP) paradigms can provide a reliable index of cognitive workload. The amplitude change of ERP components with an increase in cognitive difficulty is dependent on the features of the task. Defining difficulty levels is the most critical aspect of single task paradigms. For evaluating the cognitive workload of a single task, the stimuli should not interfere with the task. Abstract: This review appraises electroencephalograph (EEG) approaches to cognitive workload evaluation, focussing on the measurement of event-related potentials (ERPs) in single task paradigms. A systematic search was undertaken, studies were included if they used a single task paradigm with an auditory stimulus combined with ERP measures from EEG to evaluate cognitive workload in healthy adults. Nineteen articles met the inclusion criteria. There was a change in the amplitude of ERP components with an increase in cognitive difficulty. However, this change was dependent on the features of the task and stimuli. This review emphasizes the importance of stimulus and task selection in single task paradigms to evaluate cognitive workload. This review also synthesizes important concepts regarding ERPs in single task paradigms such as the effect of primary task selection on specific ERP components.